RESPONSE OF MONOPOD PLATFORM UNDER EXTREME WAVE IN MALAYSIAN WATER - Jamaluddin, Mohd Affiq (2014)
This paper investigated the structural response of an existing monopod platform under extreme wave condition in Malaysian water. The estimation of the response plays an important role in the design of offshore structure. In this investigation, in-place analysis is performed to measure the reliability of monopod structure owing to the extreme environmental load condition in Malaysian water. The response of the structure to the varying conditions of the structure and varying environmental loads directions are analysed using well defined in-place analysis method[1]. In the present analysis, the deflection of the structure is studied for the number of guyed wires supporting the structure and multi-direction of environmental loads applied onto the structure.